2008
DOI: 10.1002/ajmg.b.30726
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of schizophrenia on 18 genes involved in neuronal migration: MDGA1 as a new susceptibility gene

Abstract: Several lines of evidence support the theory of schizophrenia (SZ) being a neurodevelopmental disorder. The structural, cytoarchitectural and functional brain abnormalities reported in patients with SZ, might be due to aberrant neuronal migration, since the final position of neurons affects neuronal function, morphology, and formation of synaptic connections. We have investigated the putative association between SZ and gene variants engaged in the neuronal migration process, by performing an association study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 82 publications
4
84
0
2
Order By: Relevance
“…Knockout of MDGA1 causes a discrete phenotype in neuronal migration and impairs rostral growth of commissural axons, suggesting an important role during the initial development of the brain (17,18). Interestingly, SNP-based, large-scale human genetic analyses suggested that MDGA1 and MDGA2 may be susceptibility genes for schizophrenia, bipolar disorder, and autism spectrum disorder (19)(20)(21). However, despite continued high-level expression of MDGAs in adult brain, their functions in mature neurons remain unknown.…”
mentioning
confidence: 99%
“…Knockout of MDGA1 causes a discrete phenotype in neuronal migration and impairs rostral growth of commissural axons, suggesting an important role during the initial development of the brain (17,18). Interestingly, SNP-based, large-scale human genetic analyses suggested that MDGA1 and MDGA2 may be susceptibility genes for schizophrenia, bipolar disorder, and autism spectrum disorder (19)(20)(21). However, despite continued high-level expression of MDGAs in adult brain, their functions in mature neurons remain unknown.…”
mentioning
confidence: 99%
“…Although its impact on disease pathogenesis is debated (10,27), its connection to schizophrenia is credible (28), and its importance in corticogenesis is widely accepted (3,17,29). Likewise, evidence (30,31) associating NDEL1 to schizophrenia biology is debated (32). However, the crucial role of NDEL1, together with DISC1 in cortical layer formation (17,29), is well established.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, in the last few years both MDGA1 and MDGA2 have been implicated in human neurodevelopmental syndromes. MDGA1 has been proposed as a new schizophrenia susceptibility gene involved in neuronal migration [35], meanwhile MDGA2 has been postulated as a novel autism susceptibility gene that shows a high similarity to contactin 4 (CNTN4), which has also been linked to this disease [36]. Moreover, MDGA1 expression has been found to be altered in tumor tissues [3,37].…”
Section: Discussionmentioning
confidence: 99%